The informed consent in the mature minor: Understanding and decision-making capacity - Reyes Boceta; Olga Martínez-Casares; Marta Albert (Elsevier, 2021)
Introduction: The informed consent of the minor is a fundamental requirement of paediatric research. There is a lack of harmonisation as regards the age of the mature minor to consent, and there are no systematic tools available to assess competence in decision-making capacity. The objective of this work is to analyse the ethical and legal situation of consent by minors, as well as studies that use an objective assessment tool in the mature minor. Material and methods: Systematic review of scientific articles in PubMed, Embase and the Grey Literature, published with keywords "informed consent minors", without date restriction until March 2019. Abstracts and a selection of complete articles were reviewed following a protocol including identification, screening, eligibility, and inclusion. Results: Of the 260 records identified, 139 were excluded. After categorising the resulting 121 publications, 13 were finally selected following the eligibility criteria, including 7 articles on international ethical and legal regulations and 6 on understanding and decision- making capacity assessment. The MacArthur Competence Assessment Tool for Clinical Research (MacCAT-CR) semi-structured interview was used in 4 studies, including different age ranges (6-21 years) in healthy and sick children. Conclusions: The semi-structured MacArthur interview adapted to adolescents could be an appropriate tool with robust psychometric measures for assessing competence for the informed consent of minors between 9 and 12 years of age. The regulation of informed consent in paediatric research should consider this evidence. Resumen: Introducción: El consentimiento informado del menor es un requerimiento fundamental de la investigación pediátrica. Actualmente existe una desarmonización en cuanto a la edad del menor maduro para consentir y no se dispone de herramientas sistemáticas para evaluar la competencia en la capacidad de decisión. El objetivo de este trabajo es analizar la situación ética y legal del consentimiento en menores, así como los estudios que utilizan un instrumento objetivo de evaluación en el menor maduro. Material y métodos: Revisión bibliográfica de artículos científicos en PubMed, Embase y Literatura gris, publicados con palabras clave «informed consent minors», sin restricción de fecha hasta marzo 2019. Se revisaron los abstracts y una selección de los artículos completos siguiendo un protocolo de identificación, cribado, elegibilidad e inclusión. Resultados: De los 260 registros identificados, se excluyeron 139. Tras categorizar los 121 artículos resultantes, finalmente se seleccionaron 13 siguiendo los criterios de elegibilidad, incluyéndose 7 artículos sobre normativa ética y legal internacional, y 6 sobre evaluación de comprensión y capacidad de decisión. En 4 estudios se ha utilizado la entrevista semiestructurada McCarthur Competency Assessment Tool for Clinical Research (MacCAT-CR), en diferentes rangos de edad (6-21 años), niños sanos y con alguna patología. Conclusiones: La entrevista semiestructurada McCarthur adaptada a adolescentes podría ser una herramienta adecuada con medidas psicométricas robustas para la valoración de competencia para el consentimiento informado de menores entre 9 y 12 años. La regulación del consentimiento informado en investigación pediátrica debería ser receptiva a estas evidencias.